Removal of methylene blue by orange and uvaia seeds (JOURNAL OF ADVANCES IN AGRICULTURE, 2015)
In this study, the adsorption behavior of methylene blue (MB) was investigated using orange seed (OS) and uvaia seed (US) as low cost adsorbents. These materials were characterized using FTIR (Fourier transform infrared spectroscopy), elemental chemical analysis (CHNO), thermogravimetric analysis (TGA), zeta potential, specific surface area and a test for determination of acid sites. The parameters evaluated in the kinetic study of adsorption were contact time, initial dye concentration, mass of adsorbent and pH. The adsorption of MB onto OS and US samples could be explained by Elovich ?s kinetic model. The experimental isotherms data, carried out at the temperatures of 25°C, 35°C, 45°C and 55°C, were better represented by Sips. It was verified that the adsorption was spontaneous and endothermic according to the thermodynamic parameters ?G°, ?H ° and ?S ° evaluated. The OS and US maximum adsorption capacity at the temperature of 25°C was 38 mg g-1 and 48 mg g-1 , respectively. The reuse tests performed at three subsequent times showed that there was no significant decrease regarding the materials efficiency, therefore emphasizing its viability as biosorbents.